2014
DOI: 10.1111/1469-0691.12340
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of early childhood infection by Kaposi's sarcoma-associated herpesvirus in a minority population in China

Abstract: In China, KSHV seroprevalence varies considerably among different regions and ethnicities. But in Xinjiang province, located in the northwestern China, there is a very high seroprevalence of KSHV in adults of Kazak and Ughur ethnicities. However, KSHV prevalence in children and the risk factors associated with the acquisition of infection are currently not known. The aim of this study was to investigate the prevalence of KSHV infection, identify associated socio-economic or behavioral risk factors and the humo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The prevalence among the general population was found to be the lowest in Guangdong Province in southern China and the highest in Xinjiang autonomous region [Zhang et al, ], which is located on the ancient Silk Road as an important staging post over a 1,000 years ago and mainly consists of Han and Uygur ethnicities. The seroprevalence of KSHV was 46.6% in Uygur patients with diseases other than KS [Dilnur et al, ], and another study [Cao et al, ] reported KSHV seroprevalence in children and caregivers in Xinjiang was 48.3% and 64.7%, respectively; suggesting that KSHV infection was widespread in Xinjiang area. Moreover, some studies had reported the KSHV prevalence in Taiwan district as well.…”
Section: Epidemiology Characteristic Of Kshv In Asiamentioning
confidence: 99%
“…The prevalence among the general population was found to be the lowest in Guangdong Province in southern China and the highest in Xinjiang autonomous region [Zhang et al, ], which is located on the ancient Silk Road as an important staging post over a 1,000 years ago and mainly consists of Han and Uygur ethnicities. The seroprevalence of KSHV was 46.6% in Uygur patients with diseases other than KS [Dilnur et al, ], and another study [Cao et al, ] reported KSHV seroprevalence in children and caregivers in Xinjiang was 48.3% and 64.7%, respectively; suggesting that KSHV infection was widespread in Xinjiang area. Moreover, some studies had reported the KSHV prevalence in Taiwan district as well.…”
Section: Epidemiology Characteristic Of Kshv In Asiamentioning
confidence: 99%
“…In contrast, KS incidence is uncommon and KSHV prevalence is low in most Asian countries [ 17 ]. However, in China, KSHV prevalence varies considerably between different regions of the country and is between 7.3% percent and 16.1 percent in adults in different provinces [ 18 , 19 , 20 , 21 ]. In particular, the prevalence was found to be high in the Xinjiang province, which is located in the northwestern region of China.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the prevalence was found to be high in the Xinjiang province, which is located in the northwestern region of China. Interestingly, cases of both classic KS and AIDS-associated KS are found mostly in the Uyghurs and the Kazakh ethnicities [ 20 , 21 ]. The reasons for such geographical and population variations of KS and KSHV distribution remain to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who preferred meat were more likely to be KSHV positive, compared with individuals preferred balanced diet. We speculated that preference for meat may be associated with other behaviors that increase the probability of KSHV infection, for example, sharing food . KSHV has been detected in saliva of infected individuals, and food can be an agent of KSHV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that preference for meat may be associated with other behaviors that increase the probability of KSHV infection, for example, sharing food. 29,30 KSHV has been detected in saliva of infected individuals, 31 and food can be an agent of KSHV transmission. People who prefer meat may have a traditional custom of local Uygur, sharing food or eating hand pilaf and so on.…”
Section: Discussionmentioning
confidence: 99%